Alejandra Pizarnik e a Condessa Sangrenta: uma análise do simbólico nas ilustrações góticas de Santiago Caruso - Ribeiro, Emilio Soares (Programa de Estudos Pós-graduados em Comunicação e Semiótica - PUC-SP, 2016)
Abstract This paper focuses on the analysis of imagetic depictions made by the illustrator Santiago Caruso based on The Bloody Countess’ gothic symbols, written by Alejandra Pizarnik. It inquires how Caruso has depicted, using techniques that includes graffito, the symbols of death, blood, mirror and redness that interact to give the tale its gothic aspect, by considering important peculiarities of the language involved and how they relate to each other in the meaning construction of the artwork here studied.

Resumo O presente trabalho se volta para a análise das representações imagéticas que o ilustrador Santiago Caruso faz dos símbolos góticos da obra A Condessa Sangrenta, da escritora Alejandra Pizarnik. Considerando a importância de se analisar as peculiaridades das linguagens envolvidas e como se relacionam na construção dos significados da obra em estudo, investigamos como Caruso, utilizando técnicas que incluem o esgrafiado, representou os símbolos da morte, do sangue, do espelho e do vermelho, que interagem no conto para conferir-lhe um caráter gótico.
Alejandra Pizarnik and The Bloody Countess: an analysis of the symbolic in Santiago Caruso’s gothic illustrations
Keywords: Santiago Caruso; Alejandra Pizarnik; gothic symbols; illustration; Santiago Caruso; Alejandra Pizarnik; símbolos góticos; ilustração